The Use of Green Turtles in Bali, When Conservation Meets Culture - Westerlaken, Rodney (An1mage Jurnal Studi Kultural, 2016)
The use of green turtles in ceremonies, as delicacy or for the use of the shell has been a vast problem in history and recent years on Bali. The number of turtles living in the waters surrounding Bali is decreasing and the illegal trade is vivid.   Several projects are fighting for conservation of turtles and the Parisada Hindu Dharma Indonesia (the highest Hindu council) issued a decree against the use of turtles in ceremonies, but illegal trade remains. On April 7, 2016 40 green seaturtles (Chelonia mydas) were captured by KAPOLDA (kepolisian daerah, regional police). They were on a ship for 7 days without any water, there flippers tied together prohibiting them to move. On April 14, 2016 31 turtles were released on Kuta beach after given medical care. Four turtles died, three are currently still under medical care and three are kept as evidence. The green turtle is listed as an endangered species on the IUCN red list [1] and should be protected. Conservation and culture meet eachother at the struggle for the green turtle.